Pengaruh Live Streaming dan Kualitas Produk terhadap Keputusan Pembelian Melalui Kepercayaan Konsumen pada Aplikasi TikTokShop - Alawiyah, Shufia; Ali, Mochammad Mukti (Jurnal Nasional Manajemen Pemasaran dan SDM, 2024)
This study aims to analyze the impact of live streaming and product quality on purchase decisions through consumer trust as an intervening variable on the TikTokShop application of Butik IR Fashionstyle. Using a quantitative verificative approach, the study involved 100 samples selected through probability sampling. Data were collected via questionnaires and analyzed using multiple linear regression. The results show that live streaming has a positive and significant effect on consumer trust, while product quality has a positive but not significant impact. Simultaneously, live streaming and product quality have a significant positive effect on consumer trust, with a contribution of 46.1%. Live streaming, product quality, and consumer trust together have a significant positive effect on purchase decisions, contributing 81.3%.